Architecting Predictive Analytics-Based Dynamic Scaling Solutions for Multi-Tenant Cloud Platforms - Abdul Samad Mohammed; Manish Tomar; Vincent Kanka (Journal of Science & Technology, 2021)
The rapid adoption of multi-tenant cloud platforms has necessitated the development of efficient scaling strategies to handle dynamic, variable workloads. As cloud computing continues to evolve, platforms must effectively manage the allocation of resources across multiple tenants, ensuring that both performance and cost-efficiency are optimized. This research paper addresses the design of predictive analytics-based dynamic scaling solutions for multi-tenant cloud environments, focusing on the integration of advanced auto-scaling mechanisms, predictive models, and cost optimization techniques for shared infrastructure. The challenges associated with scaling in multi-tenant cloud environments, particularly under varying demand conditions, require a comprehensive understanding of both the technical and business aspects of cloud resource management.The primary objective of this study is to explore the architecture and mechanisms for dynamic scaling in cloud platforms using predictive analytics, a critical capability that allows platforms to anticipate changes in resource requirements before they occur. Predictive models can leverage historical usage data, tenant behavior patterns, and workload characteristics to forecast future resource demands. These forecasts can then be used to trigger auto-scaling actions, ensuring that resources are allocated in a timely and efficient manner without human intervention. This paper will delve into various predictive modeling techniques, including time-series forecasting, machine learning-based methods, and hybrid approaches, highlighting their suitability for accurate resource demand prediction in multi-tenant scenarios.One of the key components of the proposed solution is the design of an auto-scaling mechanism that responds to predicted changes in demand. Auto-scaling mechanisms, which adjust resource allocation in real-time based on workload fluctuations, play a critical role in enhancing the flexibility and efficiency of multi-tenant cloud environments. The dynamic scaling approach presented in this paper integrates predictive analytics with auto-scaling to ensure that resources are provisioned optimally, thereby preventing both over-provisioning, which leads to unnecessary costs, and under-provisioning, which can result in performance degradation and tenant dissatisfaction. The paper discusses various auto-scaling strategies, such as threshold-based, policy-driven, and machine learning-based scaling, evaluating their effectiveness in different cloud scenarios.In addition to performance and scalability, cost optimization is a significant concern in multi-tenant cloud environments, where shared infrastructure is a fundamental aspect of the platform's design. The research emphasizes cost-efficient resource management strategies, which leverage predictive analytics to minimize wastage and ensure that tenants only pay for the resources they consume. This paper will explore cost-aware dynamic scaling, which adjusts resource allocation not only based on performance needs but also with a focus on cost constraints. Techniques such as spot pricing, resource pooling, and resource consolidation will be analyzed for their ability to contribute to cost optimization while maintaining service quality. The study will also examine the trade-offs between different scaling strategies, considering both short-term and long-term cost implications.Furthermore, the integration of dynamic scaling solutions with existing cloud management frameworks, such as Kubernetes, OpenStack, and other cloud orchestration platforms, will be discussed. These platforms provide the infrastructure required for automated resource provisioning and management. The paper will highlight how predictive analytics can be integrated into these orchestration tools to enhance the auto-scaling capabilities of multi-tenant platforms. By combining predictive analytics with these frameworks, cloud providers can ensure that resources are distributed in the most effective way possible, based on predicted demand patterns and real-time workload variations.The paper also addresses the challenges inherent in designing scalable solutions for multi-tenant platforms, including issues related to resource contention, isolation, and fairness. In multi-tenant environments, where multiple users share the same physical resources, ensuring fair distribution and maintaining performance isolation between tenants are critical concerns. Predictive analytics-based dynamic scaling mechanisms must be designed to address these challenges, ensuring that tenants receive fair treatment and that resource allocation is done in a way that minimizes contention and maximizes overall platform efficiency.Real-world case studies and experimental setups will be presented to demonstrate the effectiveness of the proposed predictive analytics-based dynamic scaling solution. These case studies will illustrate how predictive analytics can be employed in different industries, such as e-commerce, finance, and healthcare, where dynamic workloads are prevalent. Performance metrics, such as response times, resource utilization, and cost efficiency, will be used to assess the efficacy of the solution in various scenarios. The paper will also compare the proposed approach with traditional static scaling methods, highlighting the advantages of dynamic scaling in terms of performance and cost optimization.The research concludes with an exploration of future directions in dynamic scaling for multi-tenant cloud platforms. The ongoing advancements in machine learning, artificial intelligence, and big data analytics offer promising avenues for enhancing predictive models and scaling mechanisms. The paper will discuss emerging trends, such as the use of deep learning for more accurate resource demand prediction and the potential for integrating blockchain technologies to ensure transparency and trust in resource allocation decisions. The conclusion will also reflect on the broader implications of dynamic scaling in cloud computing, emphasizing the role of predictive analytics in driving innovation and efficiency in cloud-based platforms.
Keywords: dynamic scaling; predictive analytics; multi-tenant cloud